2017
DOI: 10.1007/s12035-017-0493-7
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Folic Acid-Deficient or Folic Acid-Supplemented Diet in the Gestational Phase of Female Rats and in Their Adult Offspring Subjected to an Animal Model of Schizophrenia

Abstract: Although folic acid (FA) supplementation is known to influence numerous physiological functions, especially during pregnancy, little is known about its direct effects on the mothers' health. However, this vitamin is essential for the health of the mother and for the normal growth and development of the fetus. Thus, the aim of this study was (1) to evaluate the cognitive effects and biochemical markers produced by the AIN-93 diet (control), the AIN-93 diet supplemented with different doses of FA (5, 10, and 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…As expected, no differences between the FA‐supplemented and the SD diets were observed, both for food consumption and weight. Canever et al (2018) did not found differences in the weight of the pregnant rats during gestation that were supplemented with FA. Contrary to the present study, they found that FA‐supplemented dams had an increase in the food intake when compare, especially, with FA‐deficient, and this difference was associated with the vitamin supplementation itself.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…As expected, no differences between the FA‐supplemented and the SD diets were observed, both for food consumption and weight. Canever et al (2018) did not found differences in the weight of the pregnant rats during gestation that were supplemented with FA. Contrary to the present study, they found that FA‐supplemented dams had an increase in the food intake when compare, especially, with FA‐deficient, and this difference was associated with the vitamin supplementation itself.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, Sittig et al, (2012) found memory and motivation impairment in young rats that had received FA supplemented diets (5.3 mg/kg) and these data were associated to suppress thyroid hormones receptors function in the hippocampus. Canever et al, (2018) evaluated the FA supplementation during pregnancy and lactation and they found an improvement in the memory of the FA‐supplemented dams (5 and 10 mg/kg of FA) in the Y‐maze test. Despite the similarity, this study supplemented the mothers for a longer period and in different doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Folic acid plays a positive role in preventing in ammation, oxidative stress, and some diseases possibly by mediating the expression of cytokines (IL-1β, IL-6, TNF-α and others) [17,19,43,44]. During female pregnancy and lactation, appropriate folate intake reduced the expression of IL-6 and TNF-α of dams and their offspring [45]. Our in vitro experiments showed similar results that appropriately supplementary folic acid (5 µg/mL) reduced the in ammation of the mammary epithelial cells induced by either S. aureus or MRSA may through in uencing the expression of interleukins genes (IL-1β, IL-6, and IL-8).…”
Section: Folic Acid Dose-dependently Prevents Mastitis and Increases mentioning
confidence: 99%
“…, ) and pharmacological targeting of the ECS has great potential for treatment of schizophrenia (disorder, programmed by maternal folic acid deficiency (Canever et al. )), autism spectrum disorder and epilepsy (Di Marzo ). Based on the facts that epilepsy occurs naturally in baboons (Szabo and Salinas ) and these NHP express all components of the ECS (Brocato et al.…”
Section: Introductionmentioning
confidence: 99%